Sharing a common resource in a perspective of sustainable development: The case of a wood innovation system - Rachel Levy; Marie-Claude Belis-Bergouignan (European Regional Science Association (ERSA), 2010)
Based on the main specificity of the wood fili√re, i.e. its strong dependence on the wood resource, the present article focuses on how this dependence configures the Aquitaine region's wood innovation system. More particularly, we attempt to analyze the effects and impacts of the promotion of eco-innovations (innovation that is developed in an the aim to reduce environmental pollution), on a system that is characterized by the share of a natural resource. By putting the wood resource at the very heart of our analysis, our research highlights original features of the wood fili√re dynamics. The complexity of the considered innovation system leads us to think in terms of an articulation of a wood system, determined by the geographic implantation of the wood resource with a productive system. A multidimensional framework enables to underline and federate the effects of developing eco-innovations within a territorial and sectoral system that is heavily reliant on a common resource. Empirically, our research is based on the illustration provided by the qualitative in-depth analysis of 8 eco-innovation projects that emerged and developed within this wood fili√re and are carried out under the aegis of the Xylofutur 'competitiveness cluster'. Following the case study methodology, our investigation was conducted through 56 semi-directive face-to-face interviews with the main actors of this wood fili√re (companies, research laboratories, intermediation bodies). Through the example of these eco-innovation projects, we illustrate how the dependence on a natural resource exerts a deep influence on the limits and performances of an innovation system, defined at the convergence of territorial, sectoral or technological system's approaches. If this system, its actors and the innovations implemented, appears to be dependant on the resource, reversely, the resource appears to be dependant on the system's dynamics. This case study leads us to express theoretical suggestions on the necessity to integrate a resource-based approach into researches dealing with the emergence and the role of innovation systems. Moreover, this approach enables to take into account the integration of the sustainable development dimension into these systems.
Keywords: 330